2018
DOI: 10.1371/journal.pone.0205139
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human randomized controlled trial of an oral, replicating adenovirus 26 vector vaccine for HIV-1

Abstract: BackgroundLive, attenuated viral vectors that express HIV-1 antigens are being investigated as an approach to generating durable immune responses against HIV-1 in humans. We recently developed a replication-competent, highly attenuated Ad26 vector that expresses mosaic HIV-1 Env (rcAd26.MOS1.HIV-Env, “rcAd26”). Here we present the results of a first-in-human, placebo-controlled clinical trial to test the safety, immunogenicity and mucosal shedding of rcAd26 given orally.MethodsHealthy adults were randomly assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…The median NAb endpoint titer measured in the macaques was ∼40. Taken together, in both mice and macaques, the antibody responses to this live recombinant virus vector seem very weak, which is consistent with how adenovirus-based HIV-1 vaccines perform in macaques and humans unless a protein boost is given ( 90 , 91 ). All 6 of the ChAdOx1-vaccinated macaques became infected after SARS-CoV-2 challenge, although with fewer symptoms, including reduced lung damage compared to that of the control group.…”
Section: Vaccine Challenge Experiments In Monkey Modelssupporting
confidence: 66%
See 2 more Smart Citations
“…The median NAb endpoint titer measured in the macaques was ∼40. Taken together, in both mice and macaques, the antibody responses to this live recombinant virus vector seem very weak, which is consistent with how adenovirus-based HIV-1 vaccines perform in macaques and humans unless a protein boost is given ( 90 , 91 ). All 6 of the ChAdOx1-vaccinated macaques became infected after SARS-CoV-2 challenge, although with fewer symptoms, including reduced lung damage compared to that of the control group.…”
Section: Vaccine Challenge Experiments In Monkey Modelssupporting
confidence: 66%
“…In the HIV-1 vaccine arena, adenovirus vaccines induce only weak antibody responses in animals and humans compared to those from recombinant proteins, even when the endpoint is only nonneutralizing antibodies (non-NAbs) ( 82 , 90 ). Indeed, an adenovirus-based vaccine from Janssen that is now in phase 2b trials for HIV-1 prevention includes a recombinant spike-derived protein boost component that is specifically intended to increase non-NAb titers (it is unable to elicit NAbs in a meaningful way) ( 90 , 91 ). This adenovirus vector seems conceptually similar to the one that is the basis of the same company’s SARS-CoV-2 vaccine program.…”
Section: Immunogenicity Of Sars-cov-2 Vaccine Candidatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenoviruses are large double stranded DNA viruses that, through deletion of genetic content and propagation to high titers, can be used as gene-delivery tools or vaccine vectors [5]. Historically, Ad vaccines and vectors were replication competent and thus had some risk of causing an Adenoviral infection [6,7]. Modern Ad constructs are typically replication incompetent or produce single cycle infections where no new Ad particles are produced but an inserted transgene of interest is efficiently expressed [8].…”
Section: Introductionmentioning
confidence: 99%
“…Of the more than 70 known AdV types, only a small number have been tested in preclinical studies (6,7,9,(12)(13)(14)(15), and apart from Ad5, only vectors based on human AdV types 4, 6, 26, and 35 and chimpanzee AdV types 3 and 63 have been advanced into clinical studies as vaccine candidates against Ebola virus (16,17), Plasmodium falciparum (18,19), Mycobacterium tuberculosis (20), influenza virus (21), hepatitis C virus (22), or human immunodeficiency virus (HIV) (23)(24)(25)(26). For most of the rare AdV-based vectors, it has been shown that their immunogenicity is inferior to that of Ad5, resulting in reduced immune responses upon immunization with these vectors, although their efficacy in Ad5-preimmune mice is superior to the efficacy of an Ad5-based vaccine (7,9,12,14,15).…”
mentioning
confidence: 99%